2021
DOI: 10.1097/sle.0000000000000909
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Endoscopic Snare Ampullectomy for Adenomatous Ampullary Lesions: Focus on Pancreatic Stent Placement to Prevent Pancreatitis

Abstract: Background: Ampullary tumors, although relatively uncommon, are increasingly diagnosed due to ongoing progress in imaging technology and the diagnostic accuracy of endoscopic ultrasound and magnetic resonance cholangiopancreatography. Endoscopic ampullectomy (EA) has become the preferred treatment option over surgery due to its lower morbidity for benign ampullary adenomas. This study aims to evaluate the efficacy, safety, and outcome of EA in 30 patients with benign-appearing ampullary lesions with particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Thus, the best evidence to date suggests that routine submucosal injection is not warranted during endoscopic resection of ampullary adenomas. (2) Prophylactic pancreatic duct (PD) stents: In randomized trials, PD stent placement not only decreases the occurrence of post EP pancreatitis but also is lowers the rate of long-term papillary stenosis after ampullectomy [32][33][34]. An area of uncertainty is the optimal length and diameter of PD stents.…”
Section: Management Ampullary Adenomasmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the best evidence to date suggests that routine submucosal injection is not warranted during endoscopic resection of ampullary adenomas. (2) Prophylactic pancreatic duct (PD) stents: In randomized trials, PD stent placement not only decreases the occurrence of post EP pancreatitis but also is lowers the rate of long-term papillary stenosis after ampullectomy [32][33][34]. An area of uncertainty is the optimal length and diameter of PD stents.…”
Section: Management Ampullary Adenomasmentioning
confidence: 99%
“…Prophylactic pancreatic duct (PD) stents: In randomized trials, PD stent placement not only decreases the occurrence of post EP pancreatitis but also is lowers the rate of long-term papillary stenosis after ampullectomy [32–34]. An area of uncertainty is the optimal length and diameter of PD stents.…”
Section: Managementampullary Adenomasmentioning
confidence: 99%
“…Although prophylactic pancreatic stent placement is debated and failed to demonstrate a reduction in some studies[ 31 ], experts nevertheless recommend placement of prophylactic pancreatic stents for selected patients at high risk for post-ERCP pancreatitis (PEP)[ 32 , 33 ], especially those with insufficient pancreatic juice drainage after EP. A series of studies demonstrated that prophylactic pancreatic stent placement significantly decreased the risk of post-EP pancreatitis[ 34 , 35 ]. A meta-analysis showed that pancreatic stent placement decreased the odds of post-procedure pancreatitis and potentially reduced the risk of late post-procedure papillary stenosis[ 36 ].…”
Section: Endoscopic Techniquesmentioning
confidence: 99%